Development of Enantioselective Lithium-Isothiourea-Boronate–Catalyzed Matteson Homologations - Essman, Jake Z.; Sharma, Hayden A.; Jacobsen, Eric N. (Synlett, 2023)
Our group’s discovery of lithium-isothiourea-boronate–catalyzed Matteson homologations is chronicled. Chiral thiourea dual–hydrogen bond donors were initially found to promote enantioselective dichloromethyl boronate rearrangements, albeit with poor reproducibility. Systematic investigations of the fate of the thiourea led to the discovery that lithium-isothiourea-boronate derivatives were being generated in situ as highly enantioselective catalytically active species. The optimal lithium-isothiourea-boronate catalyst displays significant generality in the rearrangement of primary alkyl migrating groups, affording synthetically valuable α-chloro boronic ester products with consistently high enantioselectivities. The catalyst is proposed to act as a structurally rigid chiral framework that precisely positions two lithium cations to enable a dual-lithium–mediated chloride abstraction.1 Introduction2 Reaction Development3 Discovery of Isothiourea-Boronate Catalysts4 Synthetic Application5 Mechanistic and Computational Studies6 Conclusions and Outlook
Keywords: boronic ester; boronate rearrangement; anion abstraction; lithium-isothiourea-boronate; Lewis acid catalysis